Chagas Cardiomyopathy: An Update of Current Clinical Knowledge and Management. Issue 12 (18th September 2018) - Nunes, Maria Carmo Pereira; Beaton, Andrea; Acquatella, Harry; Bern, Caryn; Bolger, Ann F.; Echeverría, Luis E.; Dutra, Walderez O.; Gascon, Joaquim; Morillo, Carlos A.; Oliveira-Filho, Jamary; Ribeiro, Antonio Luiz Pinho; Marin-Neto, Jose Antonio
Abstract : Background: Chagas disease, resulting from the protozoan Trypanosoma cruzi, is an important cause of heart failure, stroke, arrhythmia, and sudden death. Traditionally regarded as a tropical disease found only in Central America and South America, Chagas disease now affects at least 300 000 residents of the United States and is growing in prevalence in other traditionally nonendemic areas. Healthcare providers and health systems outside of Latin America need to be equipped to recognize, diagnose, and treat Chagas disease and to prevent further disease transmission. Methods and Results: The American Heart Association and the Inter-American Society of Cardiology commissioned this statement to increase global awareness among providers who may encounter patients with Chagas disease outside of traditionally endemic environments. In this document, we summarize the most updated information on diagnosis, screening, and treatment of T cruzi infection, focusing primarily on its cardiovascular aspects. This document also provides quick reference tables, highlighting salient considerations for a patient with suspected or confirmed Chagas disease. Conclusions: This statement provides a broad summary of current knowledge and practice in the diagnosis and management of Chagas cardiomyopathy. It is our intent that this document will serve to increase the recognition of Chagas cardiomyopathy in low-prevalence areas and to improve care for patients with Chagas heart disease around the world.